Basic mechanism for biorientation of mitotic chromosomes is provided by the kinetochore geometry and indiscriminate turnover of kinetochore microtubules - Zaytsev, Anatoly V. (Mol Biol Cell, 2015)
Accuracy of chromosome segregation relies on the ill-understood ability of mitotic kinetochores to biorient, whereupon each sister kinetochore forms microtubule (MT) attachments to only one spindle pole. Because initial MT attachments result from chance encounters with the kinetochores, biorientation must rely on specific mechanisms to avoid and resolve improper attachments. Here we use mathematical modeling to critically analyze the error-correction potential of a simplified biorientation mechanism, which involves the back-to-back arrangement of sister kinetochores and the marked instability of kinetochore–MT attachments. We show that a typical mammalian kinetochore operates in a near-optimal regime, in which the back-to-back kinetochore geometry and the indiscriminate kinetochore–MT turnover provide strong error-correction activity. In human cells, this mechanism alone can potentially enable normal segregation of 45 out of 46 chromosomes during one mitotic division, corresponding to a mis-segregation rate in the range of 10(−1)–10(−2) per chromosome. This theoretical upper limit for chromosome segregation accuracy predicted with the basic mechanism is close to the mis-segregation rate in some cancer cells; however, it cannot explain the relatively low chromosome loss in diploid human cells, consistent with their reliance on additional mechanisms.